Natasha, Pierre & the great comet of 1812 [compact disc] : original Broadway cast recording - Malloy, Dave, 1976- (Reprise, 2017)
Pop superstar Josh Groban makes his Broadway debut in a show that that The New York Times called 'the most innovative and the best musical to open on Broadway since Hamilton.'